2013
DOI: 10.1049/iet-spr.2012.0380
|View full text |Cite
|
Sign up to set email alerts
|

Colour spaces effects on improved discrete wavelet transform‐based digital image watermarking using Arnold transform map

Abstract: The most digital image watermarking algorithms have nearly always been realised in red, green and blue (RGB) colour space. In this study, a secure, robust and imperceptible CDMA image watermarking scheme which uses discrete wavelet transform is proposed and tested in eight colour spaces RGB, YCbCr, JPEG-YCbCr, YIQ, YUV, hue, saturation, intensity, hue, saturation, value and CIELab to determine which colour space is more effective in watermarking algorithms based on correlation techniques and provides a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…In addition, encoding host images by ATM method and embedding watermarks in the first channel of each color space are the other criteria for increasing security. By comparing different color spaces, it could be found that in based non correlation watermarking algorithms not only our proposed formula called JPEG-YCbCr color space in [20] improves correlation and PSNR values of YCbCr color space, rather like previous work for based correlation watermarking algorithms in [14], it satisfies imperceptibility more than the other color spaces. After that, respectively, HSV, HSI, YUV & YIQ, RGB, CIELab and YCbCr color spaces have the most ability to satisfy imperceptibility requirement.…”
Section: A Imperceptibility and Transparency Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, encoding host images by ATM method and embedding watermarks in the first channel of each color space are the other criteria for increasing security. By comparing different color spaces, it could be found that in based non correlation watermarking algorithms not only our proposed formula called JPEG-YCbCr color space in [20] improves correlation and PSNR values of YCbCr color space, rather like previous work for based correlation watermarking algorithms in [14], it satisfies imperceptibility more than the other color spaces. After that, respectively, HSV, HSI, YUV & YIQ, RGB, CIELab and YCbCr color spaces have the most ability to satisfy imperceptibility requirement.…”
Section: A Imperceptibility and Transparency Experimentsmentioning
confidence: 99%
“…watermarked images were being under cropping attacks and then the extraction process of watermark on the cropped areas was performed. 532 | P a g e www.ijacsa.thesai.org In this paper, a non correlation based image watermarking scheme using DWT2 proposed and tested in eight historical color spaces: RGB, YCbCr, YIQ, YUV, HSI, HSV, CIELab and improved YCbCr color space, called JPEG-YCbCr which is presented by our formula in [20], to develop the results of previous work in [14] and achieve a comprehensive investigation on the effects of different color spaces on both based correlation and non correlation watermarking techniques. The watermarking security is more satisfactory than the similar works.…”
Section: B Robustness Experimentsmentioning
confidence: 99%
See 3 more Smart Citations